Ultrafast strong-field terahertz nonlinear nanometasurfaces - Cai Jiahua; Chen Sai; Geng Chunyan; Li Jianghao; Quan Baogang; Wu Xiaojun (Nanophotonics)
Strong-field terahertz (THz)–matter interaction permits the investigation of nonequilibrium behaviors in the nonperturbative zone. However, the unavailability of a high-field free-space THz source with high repetition rates, excellent beam quality, and high stability hinders its development. In this work, we obtain the nonlinear modulation dynamics of a “THz-nano” metasurface on silicon substrates using a time-resolved strong-field THz-pump THz-probe (TPTP) with a thousand orders local field enhancement through confining THz waves into nano-gaps (15 nm, λ/33,000). By switching the THz field strength, we successfully realize a self-modulation ∼50 GHz frequency shift, which is further verified via the TPTP ultrafast time-resolution technique. The phenomenon is attributed to the impact ionization (IMI) of the silicon substrate under the excitation of extremely confined strong THz fields in nano-gaps. Both strong-field induced intervalley scattering (IVS) and IMI effects of photodoped silicon occurring in nano-gaps and large-area substrates were also observed by 800 nm optical injection of carriers. These aforementioned findings provide a robust research platform for the realization of ultrafast time resolution nanoscale strong-field THz–matter interaction and new ideas for nonextreme laboratories to realize extreme THz science, applications, and THz nonlinear modulation device development.